Sequência didática para abordagem da Segunda Lei da Termodinâmica no ensino médio - Nogueira, Mauro Rodrigues Alves (Universidade Federal de São Carlos, 2020)
A very common characteristic of science education curricula is the expectation that students learn the proposed scientific content, its methodologies and about science itself, which includes its nature, its interaction with society and different cultures, its history and how these are different from non-scientific approaches. The use of historical context combined with experimentation in physics classes can significantly contribute to demonstrate the relationship between science and a wider world of ideas, and can motivate students to explore contemporary issues. In this work we consider the historical context to discuss the evolution of some concepts of thermodynamics, such as caloric and its consideration in Carnot's work, the emergence of heat terminology, the importance of heat engines in the industrial revolution until the establishment of the second law of thermodynamics and its most modern conception through the concept of entropy. In order to demonstrate such concepts, two experiments were used, the drinking bird and Hero's Aeolipile (Hero's engine), usually considered as the first known heat engine. The concept of heat engine was explored by the students using the second law of thermodynamics in order to verify whether the two experiments can be considered as heat engines. Through this approach and the experimental tests carried out, it was possible to show that the drinking bird is a heat engine and an excellent didactic device for the treatment of the second law of thermodynamics in the classroom, while Hero's Aeolipile cannot be considered as such. The latter can be considered as the first steam action and reaction turbine prototype in history, being useful to discuss how a rotational motion can be produced through thermal energy and pressurized steam. The activities were conducted in the classroom using the Flipped Classroom methodology, in which the moments and roles of teaching can be inverted and the content, usually taught by the teacher, can be watched in school time by the student using multimedia tools. The practical activities, normally assigned to be done at home, were carried out in the classroom in an interactive and collaborative manner. Our proposal was successful in the classroom, motivating the students to participate more actively during the activities. It has also enabled a treatment of more complex subjects of thermodynamics such as the concept of entropy. Our educational product consists of a teaching sequence to approach several concepts of thermodynamics, with particular attention to the second law of thermodynamics. It was prepared in a simplified language to better assist the high school physics teacher.
Teaching sequence to aproach the Second Law of Thermodynamics in high school.
Keywords: Ensino de Física; Termodinâmica; Sala de Aula Invertida; Physics Teaching; Thermodynamics; Flipped Classroom; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO